THE AUTOMATED CLASSIFICATION OF ANTHROPOGENOUS OBJECTS BY MATERIALS OF HIGH RESOLUTION AERIAL PHOTOGRAPH - Станкевич, С.; Васько, А. (Science-based technologies, 2012)
The two-level model for automated classification of man-made objects by high-resolution airborne imaging is presented. Also the test data processing output is described. Proposed model based on fusion of partial classifi-cations that performed using fundamentally distinct interpretation features — spectral and spatial ones.